The role of knowledge management in enhancing innovation performance: a study on literature reviews - Sari, Ade Maria Ulfah Rakhmatika; Riana, I Gede; Dewi, I Gusti Ayu Manuati; Wibawa, I Made Artha (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Determinant performance innovation can varies depending on context organization or industry certain. Many factors decider performance involving innovation combination internal and external aspects. Companies or organizations that succeed at innovation can often combine some or all of these factors to create an environment that supports the development and implementation of new ideas. This research aims to conduct a literature review study of company innovation performance. This research uses the literature study method to determine the measurement of company innovation performance of 56 articles related to innovation performance and its determining factors. The research was carried out by comprehensively identifying and conceptualizing the determinant framework for innovation performance in terms of (1) Innovativeness and attributes; (2) The impact of Ambidextrous Leadership On innovation performance; (3) Impact of knowledge management strategy on innovation performance; (4) The impact of creative self-efficacy on innovation performance; and (5) Conceptualization of determinants and their impact on innovation performance. The research results found that a company's ability to dynamically manage its resources is the main key to improving company performance. Thus, companies must have effective strategies in managing their resources and facing changes in the business environment to remain competitive.